3D in Corsini. Arte e fotografia autosterescopica - Carlucci, Valerio; Verbanaz, Remy (Archeomatica, 2015)
Experimentations of autostereoscopic photography for representation of the sculptural group of Palazzo Corsini. A synergy between art and photography that puts the viewer in a state that appreciate the cultural heritage through different channels of perception.